2020
DOI: 10.3390/ijerph17103446
|View full text |Cite|
|
Sign up to set email alerts
|

Who Reports Low Interactive Psychology Status? An Investigation Based on Chinese Coal Miners

Abstract: In mine safety and health research, psychological issues have always been neglected. This paper aims to identify the psychological perceptions of workers with respect to the mine environment and interpersonal environment across the whole production system. A survey was designed that measured the miners’ demographic details and perceptions of two affect-based interactions; three resource-based interactions for the manager, supervisor, co-worker; and three actual environment interactions. A total of 642 frontlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Therefore, they feel that they lack job security and are prone to anxiety. Han et al [34] investigated the mental health status of 642 coal miners from six coal mining companies in six provinces in China and found that the mental health status of coal miners was poor, especially among older people, those with low incomes, and low education level.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they feel that they lack job security and are prone to anxiety. Han et al [34] investigated the mental health status of 642 coal miners from six coal mining companies in six provinces in China and found that the mental health status of coal miners was poor, especially among older people, those with low incomes, and low education level.…”
Section: Discussionmentioning
confidence: 99%
“…To suit the characteristics and working practices of frontline coal miners, as well as Chinese culture, the scales used in this paper were reworded and rephrased. First, the contents and substance of the SC and SP scales were obtained from previous questionnaires [ 1 , 5 , 11 , 30 ] and other reports, and both SC and SP initially included six items. Second, we discussed the draft with 12 squad leaders employed as frontline safety supervisors in charge of safety in their production team and five full-time safety inspectors who supervise frontline miners (including the squad leaders) to ensure readability and face validity; all of these respondents worked at a state-owned coal mine located in Shanxi, China.…”
Section: Methodsmentioning
confidence: 99%
“…To that end, frontline coal miners in China, who work in a typical high-risk and labor-intensive industry and whose behavioral safety management is a key issue [ 10 , 11 , 12 ], were selected as participants. First, the relationships among the abovementioned factors were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Physical factors such as ground fracturing, principal stresses measurements, microelectromechanical systems, and other risk factors have been extensively studied for rock burst prone coal mines [3][4][5], while human factors have mostly been ignored in this area. Traditional human behavior studies for coal mine safety have concentrated on unsafe behaviors, occupational injuries, and hidden dangers [6,7]. Literature reveals that the relational quality and priority among various functional roles such as managers, supervisors, and employees are related to safety activities [6,8].…”
Section: Introductionmentioning
confidence: 99%